ANALISIS EFEKTIFITAS PAJAK REKLAME DALAM MENINGKATKAN PENERIMAAN PAJAK DAERAH DI KOTA BEKASI - Ratih Kumala (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
One source of Regional Revenue is local tax, one of which is advertisement tax. The formulation of this problem is how the effectiveness of advertisement tax on Regional Tax Revenues in the City of Bekasi in 2013-2017. This research method uses a qualitative descriptive method. The results of this study indicate that the advertising tax effectiveness is classified as not yet effective. Realization of regional tax in 2013 was 97.88%, in 2014 it decreased by 71.99%. In 2015, it decreased again by 58.80%, in 2016 it decreased again by 43.61%. 2013 decreased by 29.36%. The decline in 2013-2017 was due to the implementation of advertisement tax collection which often occurred misunderstanding between taxpayers and the government of the city of Bekasi. And some ways that can be done to achieve the target of advertisement tax revenue is to disseminate and educate about the importance of paying taxes to the public, and improve services for the convenience of taxpayers, cooperate and embrace advertising services.